Nitro functionalized Zn-Mo bimetal organic framework solid electrolyte and preparation method thereof

Through the assembly of nitro functionalized Zn-Mo bimetallic organic frame material and polymer matrix, high-purity materials are synthesized by reflux method, which solves the problems of low energy density and safety hazards of liquid electrolytes in lithium-ion batteries, and achieves high performance and Safe solid-state battery material.

CN119315091APending Publication Date: 2025-01-14SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411135074.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-19
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing lithium-ion battery liquid electrolyte has low energy density and high safety risks. The existing zinc-molybdenum bimetallic organic frame materials have complex synthesis process and low production efficiency, which affects the purity and performance of the material.

Method used

Using nitro functionalized Zn-Mo bimetallic organic frame material mixed with polymer matrix and lithium salt, high-purity metal organic frame material is synthesized by reflux method to form a composite polymer film as a solid electrolyte to enhance the migration and conductance of lithium ions. sex.

Benefits of technology

It significantly improves the conductivity and migration number of lithium ions, enhances the electrochemical stability and safety of the battery, reduces the risk of dendrite formation, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315091A_ABST
    Figure CN119315091A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrochemistry, and discloses a nitro functionalized Zn-Mo bimetal organic framework solid electrolyte and a preparation method thereof. The preparation method comprises the following steps: firstly, synthesizing Zn-Mo bimetal organic frameworks MOFs with nitro functional groups through a reflux method, blending the Zn-Mo bimetal organic frameworks MOFs with a lithium salt and a polymer to obtain viscous slurry, pouring the viscous slurry on a glass plate to cure the viscous slurry, standing, and carrying out vacuum drying at 60 DEG C to obtain the nitro functional Zn-Mo bimetal organic framework solid electrolyte. The preparation method is simple and easy to operate, and the electrochemical stability and thermal stability of the battery can be effectively enhanced; the lithium ion transference number of the prepared diaphragm is up to 0.70, the assembled lithium iron phosphate battery is 120 mAh g <-1 > under the rated capacitance of 1C, the capacity retention ratio is close to 95%, and the lithium iron phosphate battery shows good cycling stability and multiplying power.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrochemistry, and in particular relates to a nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte and a preparation method thereof. Background Art

[0002] The world's over-reliance on fossil fuels has not only accelerated the depletion of non-renewable resources, but also brought unprecedented threats to the sustainable development of human society. Faced with this urgent situation, innovative energy storage and conversion technologies have become the key to breaking the deadlock. Among them, lithium-ion batteries, as an ideal energy storage carrier for intermittent renewable energy such as wind power and solar energy, have effectively promoted the popularization and application of green energy. However, existing commercial lithium-ion batteries mostly rely on liquid electrolytes, which have disadvantages such as low energy density and safety risks, which to a large extent restrict the widespread application and commercialization of lithium-ion batteries. Solid-state electrolytes can not only significantly improve the safety performance of batteries, but also expand the electrochemical window and enhance the stability and energy density of batteries.

[0003] Metal-organic framework materials (MOFs), with their excellent structural properties such as high porosity, huge specific surface area and excellent chemical and thermal stability, have shown extraordinary potential in the field of energy storage technology. By cleverly integrating MOFs into polymer matrices as electrolyte fillers, new polymer-based ion-conducting materials have emerged, opening up a promising innovation path for energy storage materials. This combination strategy not only gives the material higher ionic conductivity and reduces the leakage risk common in traditional liquid electrolytes, but also enhances the material's flexibility and mechanical properties, making it an ideal choice for a range of electrochemical devices.

[0004] CN110776650A discloses a zinc-molybdenum bimetallic organic framework multi-level structure material and a preparation method thereof. The material is synthesized by a solvent thermal method, and zinc acetate dihydrate, dimethylimidazole and molybdic acid are mixed and reacted in an organic solvent to obtain a zinc-molybdenum bimetallic MOF with a multi-level structure. However, the solvent thermal method often takes a long time to complete during the synthesis process, resulting in low production efficiency, and the synthesis process of the multi-level structure is relatively complicated, which will affect the purity of the product. In the subsequent separation and purification process, additional steps are required, and the impurities present will affect the morphology of the crystal and the overall performance of the material, sacrificing the strength and durability of the material to a certain extent, especially in long-term cyclic use, the performance of the material may decline.

[0005] CN117247556A discloses a composite solid electrolyte material and its preparation method and application. The composite solid electrolyte material is composed of a polymer matrix, a solute salt (lithium salt or sodium salt) and a modified metal-organic framework material (MOF) as filler A. The modified MOF is prepared by coordinating the modified molecule with the metal ion center of the MOF or exchanging ligands with organic ligands. However, a simple modified MOF may affect the thermal stability and chemical stability of the MOF, thereby affecting the overall performance of the composite solid electrolyte, and the compatibility between the modified MOF and the polymer group may be affected, which may limit the ion transmission efficiency. Summary of the invention

[0006] The present invention provides a nitro (-NO 2 ) A method for preparing functionalized Zn-Mo bimetallic organic framework solid electrolyte to solve the existing shortcomings of low ionic conductivity and low ion migration number.

[0007] The technical solution of the present invention is as follows.

[0008] A method for preparing a nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte comprises the following steps Step 1: dissolve 2-nitroimidazole in N,N-dimethylformamide, and disperse it by ultrasound to prepare a colorless transparent solution; then weigh zinc acetate, 2-methylimidazole and molybdic acid in a molar ratio of 4:3:1 and dissolve them in the colorless transparent solution, and disperse them by ultrasound to prepare a milky white solution; Step 2: Heat the milky white solution to reflux, filter and separate the generated precipitate, wash it with N,N-dimethylformamide and methanol solution, and vacuum dry it to obtain a light yellow powder; Step 3: Use the light yellow powder as a filler, blend it with the lithium salt and the polymer in N-methyl-2-pyrrolidone, and evenly mix the light yellow powder, lithium salt and polymer in a certain proportion, and stir to obtain a light yellow viscous liquid; Step 4: The light yellow viscous liquid is formed into a film on a glass plate and dried to obtain a thin film; Step 5: Soak the prepared polymer film in triethyl phosphate and vacuum dry it to obtain a thin film solid electrolyte.

[0009] In the step 1, the molar ratio of zinc acetate to 2-methylimidazole, 2-nitroimidazole and molybdic acid is 4:3:3:1.

[0010] In step 2, the heating reflux temperature is 120-160° C., and the reaction time is 5-7 hours.

[0011] The polymer in step three is any one of polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile or polyvinylidene fluoride-hexafluoropropylene copolymer.

[0012] In the step 3, stirring is performed at room temperature for 40-48 hours.

[0013] In the step 5, the vacuum drying time is 12-24 hours and the temperature is 40-70°C.

[0014] In the step 4, the specific method of film making is to pour the slurry on a glass plate and make it uniform by rotating the glass plate.

[0015] The nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte prepared by the above preparation method.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention successfully assembled a high-performance composite polymer solid electrolyte material by mixing nitrated zinc-molybdenum bimetallic organic framework (MOF) materials with a polymer matrix and lithium salts. By ensuring the uniform dispersion of MOF particles in the polymer matrix, a film with stable structure and excellent conductivity is formed. Experimental results show that the addition of MOF significantly promotes the dynamic movement of polymer segments, enhances interfacial contact, and effectively accelerates the migration process of lithium ions. This optimized structure enables lithium ions to migrate more smoothly during the battery cycle, effectively avoiding the formation of lithium dendrites, thereby significantly reducing the safety hazards caused by dendrites piercing the diaphragm. This improvement not only improves the electrochemical stability of the battery, but also provides strong technical support for the development of safer and higher-performance solid-state batteries.

[0017] (2) The present invention first synthesizes a nitrated Zn-Mo metal organic framework with a highly ordered crystalline structure, and incorporates the metal organic framework material into a polymer matrix material as an electrolyte filler to form an ultra-thin polymer film that can be used as an excellent ion conductor. The present invention uses a Zn-Mo bimetallic ion transmission channel and uses a nitro group with high polarity to affect the d orbital of the Mo metal in the Zn-Mo metal organic framework through the large electronegativity of the nitro group, thereby increasing the energy of the d orbital, so that it can further hybridize with the TFSI- anion, enhance the confinement effect on the anion, promote the conduction of lithium ions, and improve the overall battery performance, so that MOFs have a high lithium ion conductivity in the battery separator layer and maintain a high coulombic efficiency after multiple cycles.

[0018] (3) The present invention adopts the reflux method to synthesize zinc and molybdenum bimetallic organic framework (MOF) multi-level structure materials. The main advantages of the reflux method include: 1. Mild operating conditions: Due to the relatively mild operating conditions, the reflux method is easier to scale up from laboratory scale to industrial production scale, which makes large-scale preparation possible. 2. Improve material purity: The reflux method can effectively inhibit the generation of impurities, thereby significantly improving the purity of the material. This is particularly important for the subsequent preparation of diaphragms, because the presence of impurities will seriously affect the mechanical properties of the diaphragm. Especially in the case of long-term cycling or high-intensity stress, impurities may weaken the stability of the solid electrolyte interface (SEI), thereby promoting the formation of lithium dendrites, resulting in a decrease in battery performance. Therefore, the use of the reflux method to prepare such materials can not only effectively avoid the shortcomings of the traditional solvent thermal method, but also significantly improve the performance of the final product. The preparation method of the present invention is simple and easy to implement. Since the selected raw materials are easy to obtain and the process is simple, the cost is low and it is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is a structural diagram of the zinc-molybdenum bimetallic organic framework crystal material according to Example 1 of the present invention.

[0020] Figure 2 This is a comparison diagram of X-ray diffraction of the nitro-functionalized Zn-Mo bimetallic organic framework crystal material according to Example 1 of the present invention.

[0021] Figure 3 This is the impedance diagram of the nitro-functionalized Zn-Mo bimetallic organic framework crystal material according to Example 1 of the present invention.

[0022] Figure 4 This is a rate diagram of Example 2 of the present invention based on a Zn-Mo bimetallic organic framework solid electrolyte with nitro functional groups.

[0023] Figure 5 This is a relationship diagram between the efficiency and specific capacity of the quasi-solid-state lithium battery with nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte prepared in Example 3 of the present invention after 70 cycles at a certain capacitance of 1C. DETAILED DESCRIPTION

[0024] The present invention will be further described below in conjunction with specific embodiments and drawings.

[0025] The preparation method provided by the present invention first synthesizes a crystal material by a reflux method, the crystal adopts a Zn and Mo bimetallic ion transmission channel, uses a nitro group with strong electronegativity, increases the lithium ion conductivity and migration number, and then blends it with a cationic metal salt and a polymer to obtain a metal organic framework composite polymer viscous liquid, which is then scraped on a glass plate and allowed to stand to obtain a metal organic framework composite polymer solid electrolyte. Specific embodiments are as follows.

[0026] Example 1 See also Figure 1 , a method for preparing a nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte, the specific steps are as follows: Step 1, weigh 2-nitroimidazole (0.6mmol, 1.44g) and dissolve it in 120mL N,N-dimethylformamide (DMF), and disperse it by ultrasound to prepare a colorless transparent solution; then weigh zinc acetate (0.8mmol, 5.3g), 2-methylimidazole (0.6mmol, 1.44g) and molybdic acid (0,2mmol, 1g) and dissolve them in the solution, and then disperse them by ultrasound for 10 minutes to prepare a milky white solution; Step 2: The milky white solution was heated to reflux at 160° C. for 6 hours; the resulting precipitate was separated by filtration and washed with N,N-dimethylformamide (DMF) and methanol solution, and vacuum dried to obtain a light yellow powder; Step 3: 0.125 g of light yellow powder as a filler was mixed with 0.125 g of lithium trifluoromethanesulfonyl imide (LITFSI) and 1 g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) in 6 MLN-methyl-2-pyrrolidone and stirred for 40 hours to obtain a milky white viscous liquid.

[0027] Step 4: Use a 500-micron scraper to apply the viscous liquid on a glass plate, and vacuum dry it at 50° C. for 20 hours to obtain a conductive film.

[0028] Step 5: After soaking the prepared polymer membrane in triethyl phosphate (TEP) for 48 hours, vacuum drying at 60°C for 24 hours to obtain a thin film solid electrolyte.

[0029] Example 2 A method for preparing a nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte, the specific steps are as follows: Step 1, weigh 2-nitroimidazole (0.6mmol, 1.44g) and dissolve it in 140mL N,N-dimethylformamide (DMF), and disperse it by ultrasound to make a colorless transparent solution; then weigh zinc acetate (0.8mmol, 5.3g), 2-methylimidazole (0.6mmol, 1.44g) and molybdic acid (0,2mmol, 1g) and dissolve them in N,N-dimethylformamide, and then disperse them by ultrasound for ten minutes to make a milky white solution.

[0030] Step 2: The milky white solution was heated to reflux at 160° C. for 6 hours; the resulting precipitate was separated by filtration and washed with N,N-dimethylformamide (DMF) and methanol solution, and vacuum dried to obtain a light yellow powder; Step 3: 0.125 g of light yellow powder was mixed as a filler with 0.125 g of lithium trifluoromethanesulfonyl imide (LITFSI) and 1 g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) in 6 mL of N-methyl-2-pyrrolidone and stirred for 40 hours to obtain a milky white viscous liquid.

[0031] Step 4: Use a 500-micron scraper to apply the viscous liquid on a glass plate, and vacuum dry it at 50° C. for 20 hours to obtain a conductive film.

[0032] Step 5: After soaking the prepared polymer membrane in triethyl phosphate (TEP) for 48 hours, vacuum drying it at 60°C for 12 hours to obtain a thin film solid electrolyte.

[0033] Example 3 A method for preparing a nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte, the specific steps are as follows: Step 1, weigh 2-nitroimidazole (0.6mmol, 1.44g) and dissolve it in 140mL N,N-dimethylformamide (DMF), and disperse it by ultrasound to make a colorless transparent solution; then weigh zinc acetate (0.8mmol, 5.3g), 2-methylimidazole (0.6mmol, 1.44g) and molybdic acid (0,2mmol, 1g) and dissolve them in N,N-dimethylformamide, and then disperse them by ultrasound for ten minutes to make a milky white solution.

[0034] Step 2: The milky white solution was heated to reflux at 140°C for 5 hours; the resulting precipitate was separated by filtration and washed with N,N-dimethylformamide (DMF) and methanol solution, and vacuum dried to obtain a light yellow powder; Step 3: 0.125 g of light yellow powder was mixed as a filler with 0.125 g of lithium trifluoromethanesulfonyl imide (LITFSI) and 1 g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) in 6 mL of N-methyl-2-pyrrolidone and stirred for 40 hours to obtain a milky white viscous liquid.

[0035] Step 4: Use a 500-micron scraper to apply the viscous liquid on a glass plate, and vacuum dry it at 50° C. for 20 hours to obtain a conductive film.

[0036] Step 5: After soaking the prepared polymer membrane in triethyl phosphate (TEP) for 48 hours, vacuum drying at 70°C for 20 hours to obtain a thin film solid electrolyte.

[0037] Example 4 See also Figure 1 , a method for preparing a nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte, the specific steps are as follows: Step 1, weigh 2-nitroimidazole (0.6mmol, 1.44g) and dissolve it in 140mLN,N-dimethylformamide (DMF), and disperse it by ultrasound to make a colorless transparent solution; then weigh zinc acetate (0.8mmol, 5.3g), 2-methylimidazole (0.6mmol, 1.44g) and molybdic acid (0,2mmol, 1g) and dissolve them in N,N-dimethylformamide, and then disperse them by ultrasound for ten minutes to make a milky white solution.

[0038] Step 2: The milky white solution was heated to reflux at 120° C. for 7 hours; the resulting precipitate was separated by filtration and washed with N,N-dimethylformamide (DMF) and methanol solution, and vacuum dried to obtain a light yellow powder; Step 3: 0.125 g of light yellow powder as a filler was mixed with 0.125 g of lithium trifluoromethanesulfonyl imide (LITFSI) and 1 g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) in 7 mL of N-methyl-2-pyrrolidone and stirred for 40 hours to obtain a milky white viscous liquid.

[0039] Step 4: Use a 500-micron scraper to apply the viscous liquid on a glass plate, and vacuum dry it at 50° C. for 20 hours to obtain a conductive film.

[0040] Step 5: After soaking the prepared polymer membrane in triethyl phosphate (TEP) for 48 hours, vacuum drying at 40°C for 12 hours to obtain a thin film solid electrolyte.

[0041] The thin film solid electrolyte obtained in Examples 1-4 was cut into small discs. This example is for CR2032 batteries, and the diameter of the cut discs is 19 mm. The small discs were placed in a glove box with a water oxygen value of less than 0.01 ppm, and lithium iron phosphate positive electrodes and lithium sheet negative electrodes were used to form lithium ion batteries. The rate performance (0.1C, 0.2C, 0.5C, 1C, 2C) and impedance (frequency 0.01-1000000 Hz) were then tested at different currents.

[0042] like Figure 2 The figure shows the X-ray diffraction pattern of the nitro-functionalized ZnMo bimetallic organic framework crystal material. It can be seen that the porosity in the structure is as high as 50%. And according to the XRD spectrum, it can be clearly seen that the crystal peak of the crystal material has an obvious characteristic peak at about 10, which proves that the crystal structure of the crystal material is orderly and has been successfully prepared. After the introduction of the nitro functional group, the diffraction peak appears at almost the same position, proving that it has been successfully synthesized.

[0043] like Figure 4As shown, it is the rate diagram of the nitro-functionalized Zn-Mo bimetallic organic framework. It can be seen that its initial capacity is 150 mAh / g, and after testing at different current densities, the capacity remains at 140 mAh / g, and the capacity retention rate is 95%.

[0044] like Figure 5 As shown in the figure, the relationship between efficiency and specific capacity of the nitro-functionalized Zn-Mo bimetallic organic framework after 70 cycles at a rated capacitance of 1 C. After 70 cycles, the discharge specific capacity of the battery is 120 mAh / g, and its coulombic efficiency remains at around 90%.

[0045] The test results show that Example 1 is the best example.

[0046] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte, characterized in that: The following steps are included Step 1: dissolve 2-nitroimidazole in N,N-dimethylformamide, and disperse it by ultrasound to prepare a colorless transparent solution; then weigh zinc acetate, 2-methylimidazole and molybdic acid in a molar ratio of 4:3:1 and dissolve them in the colorless transparent solution, and disperse them by ultrasound to prepare a milky white solution; Step 2: Heat the milky white solution to reflux, filter and separate the generated precipitate, wash it with N,N-dimethylformamide and methanol solution, and dry it in vacuo to obtain a light yellow powder; Step 3: Use the light yellow powder as a filler, blend it with the lithium salt and the polymer in N-methyl-2-pyrrolidone, and evenly mix the light yellow powder, lithium salt and polymer in a certain proportion, and stir to obtain a light yellow viscous liquid; Step 4: The light yellow viscous liquid is formed into a film on a glass plate and dried to obtain a thin film; Step 5: Soak the prepared polymer film in triethyl phosphate and vacuum dry it to obtain a thin film solid electrolyte.

2. The method for preparing a nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte according to claim 1, characterized in that: In the step 1, the molar ratio of zinc acetate to 2-methylimidazole, 2-nitroimidazole and molybdic acid is 4:3:3:

1.

3. A method for preparing a nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte according to claim 2, characterized in that: In step 2, the heating reflux temperature is 120-160° C., and the reaction time is 5-7 hours.

4. The method for preparing a nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte according to claim 3, characterized in that: The polymer in step three is any one of polyethylene oxide, polyvinylidene fluoride, polyacrylonitrile or polyvinylidene fluoride-hexafluoropropylene copolymer.

5. The method for preparing a nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte according to claim 4, characterized in that: In the step 3, stirring is performed at room temperature for 40-48 hours.

6. The method for preparing a nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte according to claim 5, characterized in that: In the step 5, the vacuum drying time is 12-24 hours and the temperature is 40-70°C.

7. The method for preparing a nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte according to claim 6, characterized in that: In the step 4, the specific method of film making is to pour the slurry on a glass plate and make it uniform by rotating the glass plate.

8. A nitro-functionalized Zn-Mo bimetallic organic framework solid electrolyte prepared according to the preparation method of claim 1.

Citation Information

Patent Citations

  • Zinc-molybdenum bimetal organic framework multilevel structure material and preparation method thereof

    CN110776650A

  • Composite solid electrolyte material and preparation method and application thereof

    CN117247556A

Cited By

  • Polymer solid electrolyte for lithium battery and preparation method of polymer solid electrolyte

    CN120978185A